Improving the fluid phase-boundary predictions of (solvent + lldpe) systems of commercial interest - Swanepoel, Riccardo Marlouw (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.